Preliminary Study on Diversity of Insect Pollinators in Navdanya Organic Farm, Dehradun, Uttarakhand, India - Jiju, J. S.; Kumar, Amit; Uniyal, V. P. (Indian Forester, 2017)
Situated adjacent to Shivaliks, foot hills of the Himalaya, the Navdanya Organic Farm (40 acres; 30Â° 19’38.78"N, 77Â°52’30.83"E; 534 m asl) in Doon valley in the Uttarakhand state, India, is known for developing its own seed bank grown for nine crops that represent country’s collective source of food security. The present communication reports a total of 19 insect pollinators belonging to five orders under 14 families from the farm during January to May, 2011, indicating rich insect pollinator diversity. The major pollinating species were Syrphid flies (Diptera: Syrphidae) (1521 individuals) followed by bees Apis mellifera (273) and Apis florae (121) (Hymenoptera: Apidae). Daucus carota (Carrot) had maximum number (19 species) of pollinating species, reaching a number of 852 individuals (36.4 % of the total) followed by Citrus aurantifolia (lemon) (12 species) and Matricaria chamomilla (chamomile (12 species). This study generates baseline information about diversity of insect pollinators in Doon valley in a managed organic farm like Navdanya.